2017
DOI: 10.1177/1744629517701860
|View full text |Cite
|
Sign up to set email alerts
|

Music for All: Including young people with intellectual disability in a university environment

Abstract: We investigated a continuing education course in creative music making, initiated to promote the inclusion of young people with intellectual disability in a university setting. Despite organizers' attempts to foster diversity within the student cohort, enrolments were almost exclusively from students who had intellectual disability. Being in the university environment, and in a place of higher learning, seemed to be valued by some. However, students' main focus was on group musicking in a dedicated music room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For the emotional component, many studies suggested that music therapy had a positive impact on the person with an intellectual disability, including a decrease in disruptive behaviours (Coyle, 2011; Hoyle & McKinney, 2015; Jaschke & Scherder, 2015; Kalgotra & Warwal, 2017; Savarimuthu & Bunnell, 2002; Urpi, 2016) and anxiety (Agheana, 2017; Hooper & Lindsay, 1990; Perry, 2003; Watson, 2016), increase in self‐esteem (Almeida et al, 2011; Coyle, 2011; Detzner, 1997; Hatampour et al, 2011; Humpal, 1991; Lewis, 2019; Moceviciene & Prudnikova, 2015; Rickson & Warren, 2018; Savarimuthu & Bunnell, 2002; Sooful et al, 2013; Wilson & MacDonald, 2019), and improved self‐expression and management of emotions (Cameron, 2017; Coyle, 2011; Graham, 2004; Savarimuthu & Bunnell, 2002; Staab &Dvorak, 2019; Tyas, 2010; Urpi, 2016). Beneficial outcomes for the development of social skills were also found in many studies (Agheana, 2017; Agrotou, 1994; Duffy & Fuller, 2000; Graham, 2004; Hashemian & Mohammadi, 2015; Hoyle &McKinney, 2015; Humpal, 1991; McLaughlin & Adler, 2015; Rickson & Warren, 2018; Surujlal, 2013). In addition, following their sessions, Almeida et al (2011) and Hatampour et al (2011) noted an improvement in collaboration, awareness of the ‘other’ and turn‐taking in interpersonal relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the emotional component, many studies suggested that music therapy had a positive impact on the person with an intellectual disability, including a decrease in disruptive behaviours (Coyle, 2011; Hoyle & McKinney, 2015; Jaschke & Scherder, 2015; Kalgotra & Warwal, 2017; Savarimuthu & Bunnell, 2002; Urpi, 2016) and anxiety (Agheana, 2017; Hooper & Lindsay, 1990; Perry, 2003; Watson, 2016), increase in self‐esteem (Almeida et al, 2011; Coyle, 2011; Detzner, 1997; Hatampour et al, 2011; Humpal, 1991; Lewis, 2019; Moceviciene & Prudnikova, 2015; Rickson & Warren, 2018; Savarimuthu & Bunnell, 2002; Sooful et al, 2013; Wilson & MacDonald, 2019), and improved self‐expression and management of emotions (Cameron, 2017; Coyle, 2011; Graham, 2004; Savarimuthu & Bunnell, 2002; Staab &Dvorak, 2019; Tyas, 2010; Urpi, 2016). Beneficial outcomes for the development of social skills were also found in many studies (Agheana, 2017; Agrotou, 1994; Duffy & Fuller, 2000; Graham, 2004; Hashemian & Mohammadi, 2015; Hoyle &McKinney, 2015; Humpal, 1991; McLaughlin & Adler, 2015; Rickson & Warren, 2018; Surujlal, 2013). In addition, following their sessions, Almeida et al (2011) and Hatampour et al (2011) noted an improvement in collaboration, awareness of the ‘other’ and turn‐taking in interpersonal relationships.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in social interactions was noted in various studies (Almeida et al, 2011; Cameron, 2017; Coyle, 2011; Hooper, 2002; Humpal, 1991; McFerran & Shoemark, 2013; Morris, 2014; Perry, 2003; Staab & Dvorak, 2019; Watson, 2014, 2016), which reduced isolation (Graham, 2004) and helped with forming new friendships (Pavlicevic et al, 2014). Music therapy could also foster the social inclusion of people with an intellectual disability in the community (Rickson & Warren, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…I think it is the beginning of a challenge, but there is much more to do. Evidence of a range of positive benefits experienced by people with ID as a result of attending university have been noted and further enhance the focus on this as a viable pathway (Hart et al, 2010; Morningstar & Shoemaker, 2018; Paiewonsky, 2011; Rickson & Warren, 2018). However, a more critical lens on this experience is welcome.…”
Section: Bourdieu's Theory Of Reproductionmentioning
confidence: 87%
“…However, a more critical lens on this experience is welcome. As a result, there are currently over 250 postsecondary program for people with ID in existence in the United States (Rickson & Warren, 2018), while within Europe, the Republic of Ireland has been at the forefront of developing options for study at university level for people with ID, with currently 10 institutions offering some program of study. One could ask whether longevity of a program or expansion across multiple HE institutions corresponds to a change in habitus; a change in the way of being and knowing; a change in expectations for people with ID.…”
Section: Bourdieu's Theory Of Reproductionmentioning
confidence: 99%
“…The authors emphasise that one of the reasons for its success is the company's focus on members' strengths. Similarly, music can promote acceptance, as Rickson and Warren [78] explored in a university music course in New Zealand. However, they also identify limitations and the need to encourage greater enrolment of nondisabled peers and other strategies to better integrate young people with IDD.…”
Section: Addressing Stigma At Multiple Levelsmentioning
confidence: 99%